Peran Analisis Karakter Calon Nasabah dalam Mengurangi Risiko Pembiayaan Bermasalah pada BPRS Lantabur Tebuireng - Firmansyah, Dio; Hidayati, Athi' (Program Studi Ekonomi Islam, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng, 2024)
This study explores the role of character analysis of prospective customers in reducing the risk of non-performing financing at Lantabur Tebuireng Sharia People's Economic Bank (BPRS), which focuses on financing for small and medium-sized communities. Given the challenges faced by BPRS related to the risk of non-performing loans, character analysis, which includes aspects of honesty, reputation, and discipline of customers, is very important. Qualitative research methods were applied to understand the interaction between the bank and the customer as well as the social factors that influence character evaluation. The results show that selecting customers with high integrity can significantly minimize the risk of non-performing loans. In addition, BPRS also implemented a monitoring system and a non-litigation approach in dealing with financing problems, which further strengthened their risk management. The findings confirm the importance of character analysis of prospective customers as a key strategy in maintaining the financial health of BPRS and supporting sustainable financing for small and medium-sized communities.